Transformasi Identitas Gerakan dari “Petani” menjadi “Masyarakat Adat”: Upaya Memahami Konflik Pembangunan Bandara Sultan Babullah di Ternate Maluku Utara” - Taib, Rinto; Soetarto, Endriatmo; Tonny, Fredian (Sodality: Jurnal Sosiologi Pedesaan, 2010)
Land conflict in Ternate have been in existence from the era of pre-independence to the present reform era. One example is the conflict over the development of Sultan Babullah Ternate Airport, which has victimized the peasant communities in the village of Tafure. This srudy used a strategy of qualitative method of research. It is intended to development of Sultan Babullah Ternate Airport, examine the formation and development of new social movements in Ternate and its relation to the issues of environmental and socio-economic impacts as well as the issues of ulayat (custom) land and the rights of custom communities, and determine to what extent the peasants’ movements could become a solution to win the peasants’ rights and at the same tme feasible as the forum to struggle for better life of peasants. This study found that the peasant communities initially launched protests to get the financial compensation for the land used for the airport and then in the next development they changed their movement identity from peasants to custom communities. It was also found that there were some factors that triggered the birth of the new social movement, for example lost farm land, lost housing land, disappearing acces to forest area, lost rights for custom land, lost houses or settlement, lost sources of livelihood or incomes, lost plantation land and cemetery, etc. The emergence of the peasants’ social movement in Ternate is motivated by equal feeling of poor life and strong desire for a change However, the management of organizational aspects have not yet fully run well such as filing, financing, and work division. In its development, the peasant’s movement has experienced some structural constraints, for example the weak position of peasants concerning the evidence of land ownership, while the cultural obstacle is the presence of internal conflicts or divisions in the movement.